Time to generalization and prediction of survival in patients with amyotrophic lateral sclerosis: a retrospective observational study. (25th March 2016) - Tortelli, R.; Copetti, M.; Panza, F.; Fontana, A.; Cortese, R.; Capozzo, R.; Introna, A.; D'Errico, E.; Zoccolella, S.; Arcuti, S.; Seripa, D.; Simone, I. L.; et al.
Abstract : Background and purpose: A strong association between time to generalization (TTG), considered as the time of spreading of the clinical signs from spinal or bulbar localization to both, and survival was recently identified in patients with amyotrophic lateral sclerosis (ALS). Thus, TTG may be used as an early to intermediate end‐point in survival studies. The aim of the present study was to test TTG as a predictor of survival in ALS. Methods: This was an observational retrospective study of ALS patients from a tertiary referral centre over a 5‐year follow‐up period. Results: In 212 ALS patients, TTG was associated with time to death/tracheostomy [R 0.62, 95% confidence interval (CI) 0.53–0.70; P < 0.001]. In a time‐to‐event analysis, longer TTG resulted in lower risk to reach a composite outcome (death or tracheostomy) both in univariate [hazard ratio (HR) 0.98, 95% CI 0.97–0.99] and multivariate Cox analyses (HR 0.98, 95% CI 0.96–0.99). TTG predicted death/tracheostomy at 4 years ( C ‐statistic 0.58; 95% CI 0.53–0.63) and at 5 years ( C ‐statistic 0.58; 95% CI 0.53–0.62). Conclusions: Based on the present results from a large clinical cohort, TTG may be used as a new early to intermediate end‐point to describe the ALS natural history. TTG may be potentially useful as a new primary outcome measure for clinical trials.